An exploratory study into various stakeholders' perceptions and experiences of participative management in a high school in the Cala district, Eastern Cape - Stofile, Attwell Mzamane (Rhodes University, Faculty of Education, Department of Education, 2006)
Although the word "participation" has been with mankind for a long time and is widely used by writers on management areas, it still remains difficult to define precisely what it means. As a result, "participation" is one of the most misunderstood and confusing ideas that have emerged from the field of human relations. This study seeks to explore the perceptions and understanding that the various stakeholders have about participative management. The purpose is to find out the meaning and interpretations the stakeholders attach to the idea of participation. This study is an interpretive case study of a Senior Secondary School in the Cala District of the Eastern Cape. A phenomenological approach was employed in data gathering using two data collection tools namely questionnaires and interviews. The collected data provided insight into stakeholders' views on participative management, highlighted challenges around the implementation of participative management, and revealed strategies to be utilized in promoting participation. The findings reveal that participation is a controversial idea that is easier said than done. There is no recipe for the implementation of a participative approach; it depends on the situation and nature of the subordinates. Furthermore, organization members need to adopt new thinking patterns in order to be responsive to change. Open communication emerges as the key to having genuine participation. However, participation still brings anxiety and fear of losing power to those managers who do not take kindly to it. It is recommended that good interpersonal relations should be maintained at all times to promote participation and that for schools to be effective, partnership with parents and stakeholders is essential.
Keywords: School management and organization -- South Africa -- Eastern Cape; Educational leadership -- South Africa -- Eastern Cape; Educational change -- South Africa -- Eastern Cape; Management -- Employee participation -- South Africa